2019
DOI: 10.1001/jama.2019.0555
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Titrating Positive End-Expiratory Pressure (PEEP) With an Esophageal Pressure–Guided Strategy vs an Empirical High PEEP-Fio2 Strategy on Death and Days Free From Mechanical Ventilation Among Patients With Acute Respiratory Distress Syndrome

Abstract: Importance: Adjusting positive end-expiratory pressure (PEEP) to offset pleural pressure might attenuate lung injury and improve patient outcomes in acute respiratory distress syndrome (ARDS). Objective: To determine whether PEEP titration guided by esophageal pressure (PES), an estimate of pleural pressure, was more effective than empiric high PEEP-FiO2 in moderate-to-severe ARDS. Design, Setting, and Participants: Phase-II randomized clinical trial conducted at 14 hospitals in North America. Two hundred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
259
2
18

Year Published

2019
2019
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(287 citation statements)
references
References 43 publications
8
259
2
18
Order By: Relevance
“…Physiologic studies confirmed that P L estimated by esophageal manometry reflects the regional P L of dependent lung areas where atelectasis predominate [28,29]. Titrating PEEP to target a positive P L at end-expiration maximizes lung recruitment and improves respiratory mechanics and oxygenation in ARDS [30], but did not improve survival in ARDS when compared to empirical high PEEP [31]. This particular technique is one of the methods proposed to achieve an "open lung approach".…”
Section: Effects Of Peep In Ae-ildmentioning
confidence: 87%
“…Physiologic studies confirmed that P L estimated by esophageal manometry reflects the regional P L of dependent lung areas where atelectasis predominate [28,29]. Titrating PEEP to target a positive P L at end-expiration maximizes lung recruitment and improves respiratory mechanics and oxygenation in ARDS [30], but did not improve survival in ARDS when compared to empirical high PEEP [31]. This particular technique is one of the methods proposed to achieve an "open lung approach".…”
Section: Effects Of Peep In Ae-ildmentioning
confidence: 87%
“…Insertion of an oesophageal balloon to measure transpulmonary pressures to set an optimal positive end-expiratory pressure can be considered in patients with moderate-to-severe obesity, although a 2019 trial in patients with ARDS did not show the benefit of this procedure in most patients. 7 Fluid management is important to consider as a measure to reduce pulmonary oedema. 8 In the absence of shock, fluid conservative therapy is recommended to achieve a negative fluid balance of 0·5 to 1·0 L per day.…”
Section: Therapy Implementationmentioning
confidence: 99%
“…The largest epidemiologic study on ARDS was conducted in 2016 and reported an overall ICU mortality of 35.3% (95%CI 33.3%-37.2%) and hospital mortality of 40.0% (95CI 38.1%-42.1%) [7], similar to what we observed in the standard protocol-based cohort treated according to the ARDSnet protocol. In 2019, two large randomized US trials in ARDS reported a mortality rate at 1 year of 44% [26] and at 90 days of 42% [25]. MGH was part of those two studies.…”
Section: Major Findingsmentioning
confidence: 99%
“…Further, as mentioned in the "Methods", none of our patients were enrolled in any MGH clinical trials. Although we cannot exclude other factors beyond our knowledge that might have affected the outcomes in the two cohorts, we know that, accounting for patients enrolled in trials, ARDS mortality did not change at MGH over the past 10 years (unpublished data) and did not change in the most recent US ARDS trials [25,26].…”
Section: Limitationsmentioning
confidence: 99%